Strategic information systems planning among public institutions of higher learning in Malaysia: With particular reference to Universiti Utara Malaysia - Ismail, Noor Azizi; Raja Mohd Ali, Raja Haslinda; Mat Saat, Rafeah; Mohamad Hsbollah, Hafizah (Universiti Utara Malaysia, 2007)
This study is divided into two parts.The first part of the study explores the current status, problems and benefits of strategic information systems planning (SISP)implementation among all seventeen public institutions of higher learning in Malaysia.More specifically, it investigates the perceptions of the Director of Computer Center of each institution toward the importance and also the compliance to each of the 37 tasks outlined in the Malaysian Public Sector Information and Communication Technology Strategic Plan.The second part of the study investigates the current status of IT developments and SISP initiative at Universiti Utara Malaysia (UUM).First, it investigates the users’ perceptions toward computer-based information systems at UUM.Second, it investigates the current practices of IT governance, funding and structure at UUM.For this purpose, dual but mutually supportive strands of investigations, i.e. questionnaire survey and interviews, were carried out. Findings from the first part of the study suggest that Malaysian public institutions of higher learning are beginning to acknowledge the importance of SISP.Whilst only one institution had implemented SISP, fifteen others are either at the implementation or the planning stage.These institutions are suggested to devote more time, efforts and resources to successfully implement the SISP initiatives. Findings from the second part of the study suggest that most users of UUM computer-based information systems are fairly satisfied with the current systems.However, there are still rooms for improvement especially issues related to decision support systems and IT governance, funding and structure.To be a leader in the use and application of IT, it is suggested that UUM needs a more comprehensive and well-coordinated IT strategic plan, backed by strong commitments to action from all campus community including the top management, users and service providers.